2014
DOI: 10.1007/s00704-014-1270-4
|View full text |Cite
|
Sign up to set email alerts
|

Fog climatology in Latvia

Abstract: Fog has been recognised as a hazardous weather phenomenon that can cause accidents and affect urban air quality negatively. Therefore, assessing the characteristics of fog formation, as well as the changes in fog frequency and intensity as a result of climate change is of high importance. This study covers a 52-year period and contains an analysis of the frequency of fog occurring, long-term changes in fog frequency and atmospheric conditions that favour the occurrence of fog events in Latvia. During the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Akimoto and Kusaka (2015) studied the climatological characteristics of fog in Japan and the results indicated that the numbers of foggy days decreased at many of the observation sites during a 40-year period from 1966 to 2005. The decreasing trend of fog frequency was also found in Latvia across a 52-year period (Avotniece et al, 2015). Dense fog with visibility less than 400 m seems to be reduced in many parts of the world (LaDochy and Witiw, 2012).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Akimoto and Kusaka (2015) studied the climatological characteristics of fog in Japan and the results indicated that the numbers of foggy days decreased at many of the observation sites during a 40-year period from 1966 to 2005. The decreasing trend of fog frequency was also found in Latvia across a 52-year period (Avotniece et al, 2015). Dense fog with visibility less than 400 m seems to be reduced in many parts of the world (LaDochy and Witiw, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, studies on the changes in frequency and intensity of fog caused by climate change are of high importance (Avotniece et al, 2015). During 1959-2014, a significant decreasing trend was detected in the frequency of foggy days in most regions of China, and foggy days increased firstly and then decreased continuously in some regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only long term fog climatologies that have been developed recently were simply derived using interpolation techniques on observational in situ measurements for single countries [12] or the climatology was limited to single locations [13,14]. Avotniece et al [15] used a combination of in situ measurements and a geostationary satellite cloud product to derive fog frequencies. However, only seasonal average cloud products were used and the computed output was limited to Latvia.…”
Section: Introductionmentioning
confidence: 99%
“…In Katowice and Kraków fog was clearly related to anticyclonic types with air advection from the southeastern sector (Sa, SEa) and nonadvective types Ca and Ka, while in Latvia (Avotniece et al 2015) the most favourable conditions for fog formation exist during anticyclonic situations with air advection from S, SW and W. Anticyclonic conditions also favoured fog occurrence in Oxford in the winter season (Gomez and Smith 1984). Moreover, the long-term variability of fog frequency in Latvia in the 52-year-long period of 1960-2012 was similar to that in Kraków (Avotniece et al 2015).…”
Section: Discussionmentioning
confidence: 96%